Determinants of management training in small and medium-sized businesses: some stylised facts on the influence of managers' individual characteristics. (22nd August 2011) - Neirotti, Paolo; Paolucci, Emilio
Management training and development have been recognised as a critical antecedent for the competitiveness of medium-sized enterprises given their key role in nurturing firms' innovation capabilities. There is broad empirical evidence, however, showing that such companies are reluctant to make these investments and exhibit a critical shortage of managerial and entrepreneurial skills. To examine this issue further, we investigated managers' jobs and their attitudes towards training using a sample of 131 Italian medium-sized companies. We present new evidence of the determinants of management training in medium-sized firms, indicating a greater aptitude for training among managers who are involved in peer networking, have a more specialised human capital in management, and those who are used to delegate technical and operational tasks. We also show that for the majority of managers entrepreneurial orientation is marginally important to their work, but it affects the propensity to continuous training, especially towards rapid and bit-sized forms of training. These results have considerable managerial and policy-making implications for how to bridge the shortage of managerial skills in SMEs in general.